Modeling the relationship between the moral charter derived from Islamic teachings and performance with the mediating variable of employees' perception - leila jahantigh; Abbas Babaeenezhad; Mohsen Zayandehroudi; saeed sayadi (مدیریت و چشم انداز آموزش)
AbstractThe purpose of this research is to model the relationship between the moral code derived from Islamic teachings and performance with the mediating variable of employees' perception. The current research is applicable in terms of purpose, and survey type in terms of nature and method. The statistical population of the present study includes the employees of Sistan and Baluchistan province as many as 48011 thousand people. The collection tool in the current research includes the organizational equality perception questionnaire by Astron (2015). The reliability of the research was checked and confirmed using Cronbach's alpha criterion in SPSS software. AMOS software was used to fit the conceptual model of the research. The results of the exploratory analysis confirmed the mediating role of employees' perception in the effect of the moral charter derived from Islamic teachings on organizational performance. The results show that the code of ethics derived from Islamic teachings has a positive and significant effect on organizational performance (β=0.247, p-value<0.05), and the (partial) mediating role of employees' perception on the relationship between moral code derived from Islamic teachings and organizational performance was confirmed.Extended abstractIntroductionProfessional ethics is one of the fields that have a close relationship with value and belief bases. Man is the fundamental factor of movement and transformation in the organization/department, and attention to this important and strategic factor in the work environment and activities will lead to a series of growth and excellence. Therefore, professional ethics will play an important role in this field with regard to the solutions to improve intra-organizational communication (Mehdizadeh Rostam et al, 2020). Based on this, professional ethics can be seen as the supervisor's behavior and attitude towards other workers within the organization and even with people outside the organization (Hebenstreit et al, 2018). In the 1990s, a wave of voluntary corporate codes emerged, activated by efforts to improve reputation and avoidance of companies from scandals and unethical scandals (Kaptein, 2004). Lack of commitment to ethical and Islamic principles has a positive effect on the initiation, facilitation and expansion of administrative corruption (Morre, 2008). One of the most common employee problems and issues that the management is widely faced with is dishonesty and fraud at work. Research shows that 90% of employees are dismissed due to theft and 88% of them are dismissed due to lying. These cases show the deepening of work ethic norms within organizations (Javadin & Jalilian, 2021). For the proper movement of any organization, it needs to understand and manage the ethical and professional attitude of its employees (Yaqoubi et al, 2020). In Islamic societies, morals and religious values ​​are considered as an essential part of people's culture and identity. Examining the effect of the code of ethics on the performance of employees based on Islamic teachings helps to gain a better understanding of the impact of religious values ​​on individual and organizational behavior and performance, and defines the performance of employees as a standard of progress, overtime, reward, punishment, revision and salary changes. This research seeks to answer the question: "What is the relationship between the code of ethics derived from Islamic teachings and organizational performance, and does the employees' perception of this code of ethics play a role in this relationship?"Theoretical FrameworkCode of ethics in IslamIslam is the last and most complete heavenly religion that addresses all aspects of human life (Fayaz, Mehrabani, 2016). Institutions and business organizations are more inclined to acknowledge consequential ethics than statutory ethics, and the reason is partly due to the persuasive arguments of Adam Smith, the Scottish political economist and moral philosopher. He believed that the personal benefit of a human kind is the providence of God, not the will of the state. Smith presented the fourth philosophy of natural liberty, which represents the classical argument for open market competition and free trade. In this framework, people should be allowed to pursue work that is of personal and economic benefit to them, and the natural efficiency of the labor market serves the improvement of society. Another part of those ideas is presented through spiritual ethics. Theories of ethical writing emphasize the character of the individual and the intention of the actor, as opposed to the character of the action itself or the consequences of the action. These theories emphasize the ethics of piety and are based on Aristotle's approach to character. Robert Solomon is one of the most famous proponents of this Aristotelian approach to business ethics. He favors theories of business ethics that focus on individuals within companies, so he emphasizes both corporate roles and personal piety. The center of Aristotle's view for the inner character and piety of being a person on the behavior or actions of a person; so, a good person who has acted rightly through piety is a person with perfection, and eventually has good moral standards (Nelson et al, 2011).Kozáková et al, (2021) investigated factors affecting the prevalence of ethical codes: evidence from Slovakia. Their findings showed that first, companies with less ethical codes use general terms. When they want to specialize in ethical issues, the scope should be wider. Second, companies with fewer employees do not need extensive codes of conduct because of the clear rules that are directly known to the owners. In multinational companies, the communication of ethical rules is realized through ethical codes with specific objectives, because a direct way is impossible. Third, foreign-owned companies use different management approaches and therefore codes of ethics differ in terms of extent and content.Fallahi (2021) investigated a research entitled professional ethics in education and training centers, emphasizing the statement of the second step of the Islamic revolution. 5 categories of professional ethics; individual, social, training, education, education and training centers are important, as well as the values ​​of professional ethics will lead to self-improvement in the first degree, and in the second degree, to community building, and in the third degree, to civilization.Research methodologyThe current research is applicable in terms of purpose, and survey type in terms of nature and method. The statistical population of the present study includes the employees of Sistan and Baluchistan province in the number of 48011 thousand people, due to the large sample size, 384 employees in the cities of Zabul, Zahedan and Khash were considered as sample, using the Morgan Karjesi table. The collection tool in the current research includes the organizational equality perception questionnaire by Astron (2015).Research findingsSPSS and AMOS software were used to analyze the data. The results of the exploratory analysis confirmed the mediating role of employees' perception in the effect of the moral charter derived from Islamic teachings on organizational performance. The results show that the code of ethics derived from Islamic teachings has a positive and significant effect on organizational performance (β=0.247, p-value<0.05), and the (partial) mediating role of employees' perception on the relationship between moral code derived from Islamic teachings and organizational performance was confirmed.ConclusionThe current research was conducted with the aim of modeling the relationship between the moral code derived from Islamic teachings and performance with the mediating variable of employees' perception. The results of this research are in agreement with the research results of Kozáková et al, (2021), Fallahi (2021), Mehdizadeh Rostam et al, (2020), Yaghubi et al, (2020), Rezaei Kilidbari et al, (2020), Atak & S1k (2019), and Sagheb Esmaeelpour et al, (2019). (Sagheb Esmaeelpour et al, 2019) conducted a research on mentioned topic. The results showed that there is a significant positive relationship between work ethic and its dimensions with the job performance of employees. Considering the direct relationship between work ethics and job performance, it can be said that the promotion of employees' work ethics is associated with the increase of employees' performance; therefore, it is suggested to improve the status of work ethics and job performance of employees. More attention should be paid to work ethics in various dimensions of cognitive programs and organizational learning so as to increase the performance and active participation of employees in organizational affairs and to fulfill individual responsibilities; and the managers of universities and subordinate centers should pay serious attention to the various ethical dimensions of administrative therapy employees in order to increase the level of their employees' job performance and try to improve the moral level of employees by holding training workshops, forming problem solving teams and encouraging their employees.According to the results of the research, the following suggestions are presented:According to the Islamic teachings, the moral charter can become a program to transform the global threat into a global opportunity for the advancement of human culture and the excellence of human life. With the rich culture of Islam and the useful experiences of the ancient Iranian civilization, Iranian business organizations can play an important role in promoting global ethics in business; the Islamic code of ethics makes organizations better deal with economic, political and cultural crisis; ethical organizations in Islamic business insist on respecting the rights of employees in addition to the rights of customers, and based on their rights, they begin to formulate their ethical duties. Finally, it helps the organizational personnel to achieve organizational goals by simplifying their work with greater effectiveness.